Access to and Utilization of Breast Cancer Prevention Information Among Market Women in Awka, Anambra State - Onwuka, Ifeyinwa Stella; Agbanu, Venatus Nosike (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study examines market women’s access to and utilisation of breast cancer prevention information in Ikoka Market, Awka, Anambra State. Adopting a qualitative research approach, in-depth interviews were conducted with 32 market women, selected based on data saturation principles. The findings reveal a high level of awareness of breast cancer but limited knowledge of specific preventive measures. Healthcare facilities, particularly antenatal and postnatal clinics, were identified as the primary sources of information, while mass media played a minimal role. Despite awareness, the utilisation of preventive practices such as breast self-examinations and screenings remained low due to financial constraints, low literacy levels, fear, and economic activities. The study highlights the gap between awareness and actionable knowledge, underlining the need for targeted, community-based interventions. It recommends mobile screening units, simplified health messages, and the integration of breast cancer education into market associations and social gatherings to enhance participation and accessibility.